Evidence that FGFRL1 contributes to congenital diaphragmatic hernia development in humans. Issue 3 (14th January 2021) - Gofin, Yoel; Mackay, Laura Palmer; Machol, Keren; Keswani, Sundeep; Potocki, Lorraine; Di Gregorio, Eleonora; Naretto, Valeria Giorgia; Brusco, Alfredo; Hernandez‐Garcia, Andres; Scott, Daryl A.
Abstract: Fibroblast growth factor receptor‐like 1 ( FGFRL1 ) encodes a transmembrane protein that is related to fibroblast growth factor receptors but lacks an intercellular tyrosine kinase domain. in vitro studies suggest that FGFRL1 inhibits cell proliferation and promotes cell differentiation and cell adhesion. Mice that lack FGFRL1 die shortly after birth from respiratory distress and have abnormally thin diaphragms whose muscular hypoplasia allows the liver to protrude into the thoracic cavity. Haploinsufficiency of FGFRL1 has been hypothesized to contribute to the development of congenital diaphragmatic hernia (CDH) associated with Wolf‐Hirschhorn syndrome. However, data from both humans and mice suggest that disruption of one copy of FGFRL1 alone is insufficient to cause diaphragm defects. Here we report a female fetus with CDH whose 4p16.3 deletion allows us to refine the Wolf‐Hirschhorn syndrome CDH critical region to an approximately 1.9 Mb region that contains FGFRL1 . We also report a male infant with isolated left‐sided diaphragm agenesis who carried compound heterozygous missense variants in FGFRL1 . These cases provide additional evidence that deleterious FGFRL1 variants may contribute to the development of CDH in humans.